Answer:
A. (2, -1)
Step-by-step explanation:
(4x - 9) - x = -3
3x - 9 = - 3
3x = 6
x = 2
y = 4(2) - 9
y = 8 -9
y = - 1
(2, -1)
Check
-1 - 2 = -3
Answer:
26
Step-by-step explanation:
just subtract 15 from 41 and you get 26 :)
Answer:
∠T = 67.5
∠V = 22.5
Step-by-step explanation:
Angles of a triangle rule: The angles of a triangle should add up to equal 180
That being said we create an equation to solve for x
180 = 3x + x + 90 ( there is a right angle indicated by the square at the bottom right of the triangle. A right angle has a measure of 90 degrees so that is where the 90 cam from )
Now that we've created an equation we want to solve for x
180 = 3x + x + 90
step 1 combine like terms
3x + x = 4x
now we have 180 = 4x + 90
step 2 subtract 90 from each side
180 - 90 = 90
now we have 90 = 4x
step 3 divide each side by 4
4x / 4 = x
90 / 4 = 22.5
we're left with x = 22.5
Now we want to find ∠T and ∠V
To do so we replace x in the given expressions with 22.5
for ∠V
∠V = x so ∠V = 22.5
for ∠T
∠T = 3x
* replace x with 22.5 *
3 (22.5) = 67.5
Hence ∠T = 67.5